From Ideals to Realities: Women's Access to Land in The Mining Areas in East Kalimantan - Grizelda; Haris Retno Susmiyati; Wiwik Harjanti; Dewi Atriani; Khairunnisa Noor Asufie (Faculty of Law, Mulawarman University, 2025)
Land is a basic human right, including for women. As a living space, land occupies a strategic position in the fulfillment of human rights. Constitutionally, women's equal rights to land are guaranteed by law, but in reality, it is neglected and lacks recognition and protection, especially in the natural resource extraction area. Economics that rely on mining extraction have the consequence of widespread ecological and environmental crises that affect people's lives, including vulnerable groups of women. The gender inequality in tenure, ownership, access and control over land has many impacts on women's lives. This research focuses on the law guarantees the recognition and protection of women's human rights to land, and the reality of recognition and protection of women's human rights to land in mining areas. The research findings show that ideally the law provides recognition of equal rights between women and men in access, control, and ownership of land. However, mining regulations provide more convenience for mining business actors, not ensuring protection for the community, especially women. In addition, the male paradigm as the head of the family has led to the marginalization of women in decision-making related to their land and living space. In the midst of conflicts in mining areas, efforts to assert rights and struggle for women's basic rights to land often receive discriminatory treatment and gender bias. The ecological crisis situation is a problem for the protection of women's human rights to land in mining extraction areas.